Full-scale tests on pressure characteristics of fast subways in tunnels - GONG Yanqing; GAO Hongrui; LIU Tanghong (机车电传动)
To study the "train-tunnel" coupling aerodynamic characteristics of a fast subway train running in a tunnel, full-scale tests were carried out on the Hangzhou-Haining intercity railway to study the pressure changes inside and outside the train when the train passing through the tunnel at the speeds of 100 km/h and 120 km/h. The peak-to-peak values of the pressure and the amplitudes of the pressure change in 3 s and 1.7 s were calculated. The pressure changes inside and outside the train during the process of entering and exiting the tunnel was compared. The influence of the different train formation types and different train speeds on the pressure changes inside and outside the train were analyzed, the relationship between the state of the air conditioners and the interior pressure change was researched. The research results show that the pressure change amplitudes of the rapid subway trains entering and exiting the tunnel are similar; When the train enters and runs in the tunnel, the interior pressure change rate in the tail car is the fastest. The peak-to-peak value of the exterior pressure gradually decreases from the head car to the tail car, while the peak-to-peak value of the interior pressure remains basically unchanged along the length of the vehicle. The comparison of internal and external pressures of trains with different speeds should be carried out in the non-dimensional time. The peak-to-peak value of the pressure inside and outside the train increases, and the pressure change rate accelerates with the increase of the train speed. Turning off the air conditioners could significantly reduce the interior pressure change rate of the train , which provides a reference for comfort research.